2017
DOI: 10.1111/cbdd.12910
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, cytotoxic activity, and 2D‐ and 3D‐QSAR studies of 19‐carboxyl‐modified novel isosteviol derivatives as potential anticancer agents

Abstract: Two series of novel acylthiosemicarbazide and oxadiazole fused-isosteviol derivatives were synthesized based on the 19-carboxyl modification. The target compounds were evaluated for their cytotoxicities against three cancer cell lines (HCT-116, HGC-27, and JEKO-1) using an MTT assay. Lead compounds from the acylthiosemicarbazides (4) showed IC values in the lower micromolar range. For example, compounds (4i, 4l, 4m, 4r, and 4s) exhibited significant inhibitory activities against the three cell lines with IC va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…The results suggest that the chemoinformatics QSAR approach relying on a ligand-based methodology either based on the molecular structures or the NMR spectra, corroborated with an experimental approach and could be used to predict new compounds inhibitors against the human colon carcinoma HCT116 cell line. To our knowledge, the QSAR regression model developed here, Approach A, is the largest study ever performed with regard both to the number of compounds involved and to the number of structural families involved in the modeling of inhibitory activity against HCT116 [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. The performance achieved by the NMR QSAR classification model, Approach B, allowed us to conclude that it was an excellent effort and a useful tool for dereplication to be developed if this study is extended to a high number of samples containing crude extracts, fractions and mainly pure compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggest that the chemoinformatics QSAR approach relying on a ligand-based methodology either based on the molecular structures or the NMR spectra, corroborated with an experimental approach and could be used to predict new compounds inhibitors against the human colon carcinoma HCT116 cell line. To our knowledge, the QSAR regression model developed here, Approach A, is the largest study ever performed with regard both to the number of compounds involved and to the number of structural families involved in the modeling of inhibitory activity against HCT116 [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. The performance achieved by the NMR QSAR classification model, Approach B, allowed us to conclude that it was an excellent effort and a useful tool for dereplication to be developed if this study is extended to a high number of samples containing crude extracts, fractions and mainly pure compounds.…”
Section: Discussionmentioning
confidence: 99%
“…More than fourteen Food and Drug Administration (FDA)-approved drugs were mainly CADD-driven drugs [ 7 , 8 , 9 ], e.g., Imatinib (Gleevec ® , Novartis, East Hanover, NJ, USA) a tyrosine-kinase inhibitor (anticancer approved drug, in 2001) that was developed using a multi-targeted drug design approach [ 8 ]. However, only few studies were reported on CADD for the inhibitory activity against HCT116 human colon carcinoma cells, which used small data sets that are generally focused on a single family of compounds e.g., flavonoid [ 10 , 11 , 12 ], pyrazole and furanopyrimidine [ 13 ], dispiroindoles [ 14 , 15 ], 2-pyrazolinyl-1-carbothiamide [ 16 ], N -acylbenzenesulfonamide [ 17 ], 6-chloro-1,1-dioxo-1,4,2-benzodithiazine [ 18 ], isosteviol [ 19 ], benzothiazole and pyrimido[2,1B]benzothiazole [ 20 ], 5,10,15,20-tetraaryl- and 5,15-diaryl-porphyrins [ 21 ], and platinum (IV) complexes [ 22 ] derivatives. Some studies built 3D quantitative structure–activity relationship (QSAR) approaches, by carrying out comparative molecular field analysis (CoMFA) and/or comparative molecular similarity indices analysis (CoMSIA), to design lead-like inhibitors against HCT116 cells [ 10 , 11 , 13 , 16 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxic activity of isosteviol increases when isosteviol analogues have amino alcohol and thiourea groups and it was observed that they are active against three human cancer cell lines. Each of the derivatives of isosteviol discovered showed preferable cytotoxic activity over their precursor compound [72].…”
Section: Pharmacological Activities Of Isosteviol Derivativesmentioning
confidence: 99%
“…On the other hand, a thiosemicarbazide core is present in many derivatives with diverse biological activities (Figure ). For example, 1‐(4‐chlorophenylacyl)‐4‐arylthio semicarbazide derivatives 1 have been reported as urease inhibitors (Ali et al, ), novel indole‐based thiosemicarbazides 2 act as antiviral agents (Cihan‐Üstündağ, Gürsoy, Naesens, Ulusoy‐Güzeldemirci, & Çapan, ), diacyl thiosemicarbazides 3 are potent Gram‐positive antibacterial agents (Paneth et al, ), butylated hydroxytoluene derivatives 4 function as potential antioxidants (Ariffin, Rahman, Yehye, Alhadi, & Kadir, ), 5 have antimicrobial and antitubercular activities (Rane et al, ), and 19‐carboxyl‐modified novel isosteviol derivatives 6 exhibit antineoplastic activity (Liu et al, ).…”
Section: Introductionmentioning
confidence: 99%